Investigation of biomechanical factors in track and field javelin performance: a multidimensional analysis of predictive variables through multiple regression analysis - Gil, H.-J.; Yang, J. J.; Park, J. C.; Lee, Y. S.; Park, J. M. (Korean Journal of Sport Biomechanics, 2023)
Objective: The purpose of this study is to investigate the effects of human motion and javelin kinematics during the energy transfer in javelin throwing on records, and to provide evidencebased training insights for athletes and coaches to enhance records. Method: Three javelin throw athletes (age: 22.67 ± 0.58 years, height: 178.33 ± 7.37 cm, weight: 83.67 ± 1.15 kg) were recruited for this study. Each athlete attempted ten maximum record trials, and the kinematic data from each performance were analyzed to determine their influence on the records. The Theia3d Markerless system was used for motion analysis. Results: Key factors were modeled and identified at each moment. In E1, main variables were COM Y (ß 8.162, p<.05) and COM velocity Z (ß -72.489, p<.05); in E2, COM X (ß -17.604, p<.05); in E3, COM X (ß -18.606, p<.05), COM velocity Y (ß 38.694, p<.05), and COM velocity X (ß 66.323, p<.05). For the javelin throw dynamics in E3, key determinants were Attitude angle and Javelin velocity in the Y-axis. Conclusion: The study reveals that controlled vertical movement, center of mass management during braking, and enhanced pelvic rotation significantly improve javelin throw performance. These kinematic strategies are critical for record enhancement in javelin throwing.